Pemanfaatan Peninggalan Sejarah di Riau Menuju Daerah Ekoeduwisata - Wilaela Wilaela (Lembaga penelitian dan pengabdian kepada Masyarakat, 2018)
Utilization of historical relics in the Riau region has a foundation in Law No. 11 of 2010 in the spirit of preservation of cultural heritage. Preservation requires the use, utilization and necessity of community involvement. Every effort to use cultural heritage must pay attention to the preservation of nature and the surrounding environment. Educational aspects for each tourism policy must be included and included in the curriculum and learning in schools. In Riau, efforts have been made to make a complete cultural heritage with its eco-tourism as part of tourist destinations. These efforts are carried out by the community, both individually and in the form of communities. Various efforts that are growing in this area require guidance and assistance from the government. There are groups of people who are active in the utilization of historical heritage, but they have not received attention and have not been cooperated by the government in order to develop the people's economy through ecotourism. preservation of cultural heritage. There are focus and priority, such as Siak Regency, but there are some who still have not relied on the nature-based tourism sector as a regional asset. However, in various circles, both government and society, the desire to make historical heritage as an eco-tourism destination is growing.